Visual-Based Reconstruction and Adaptive Reuse for Heritage Revitalization under Data Constraint: (Case Study: Deli Sultanate Assembly Building) - Nasution, Meyga Fitri Handayani; Novalinda; Putri, Cherisa Adelia (RUAS, 2026)
The loss of historic buildings due to urban transformation and limited documentation poses a major challenge for heritage conservation, particularly in architectural reconstruction and long-term sustainability. This study develops a visual-based reconstruction approach for data-limited conditions through a case study of the former Deli Sultanate Assembly Building in Medan. Using a qualitative Design-Based Research approach, the study integrates photographic evidence, morphological analysis, typological inference, and proportional estimation into an uncertainty-controlled reconstruction model to minimize speculative interpretation. The findings demonstrate that a high level of interpretive reliability can be achieved through systematic visual analysis and typological validation. The integration of adaptive reuse and contextual interventions enables the reconstructed building to function as a sustainable cultural and tourism center. The study proposes an integrated framework that links architectural reconstruction, functional adaptation, and contextual design, thereby bridging the gap between reconstruction and sustainability. Its novelty lies in integrating uncertainty-controlled reconstruction with adaptive reuse into a single, replicable workflow that has not been explicitly developed in the existing heritage conservation literature.